Key processes for the construction of an informal guide to develop digital competences: support resettled refugees in active job search - Trindade, A. (2021)
Any kind of learning program requires a set of processes to make sure that learning can happen in a specific environment. This means that it is important to identify the method and instructional model that can help learners getting engaged in a specific theme, in this case in developing digital competences. In this work, we present the method followed to build an informal Guide for refugees to develop digital competences, to support their active job search (which is part of an ongoing Ph.D. project). Hence, the five processes of Cognitive Theory of Multimedia Learning were used (i.e. selecting words; selecting images; organizing images; organizing words; integrating) to present text, graphics, video and audio information for optimal learning. For the creation of this informal Guide, an analysis model was developed to support the research process, namely the design of the questionnaires used to collect data. The study was divided into three phases: in phase 1, data were collected to characterize the participants (in terms of their earlier learning; their proficiency in Portuguese; their professional activity in their country of birth; their professional activity in Portugal; the computing devices they have and use). After collecting these data, the respondents (refugees) with an active profile were identified and invited to participate in the study. In phase 2 type of online social networks used by the respondents with an active profile were identified, as well as the digital competences they assume to have developed), so that in phase 3 we could conceive and carry out training sessions, with the inputs from experts, to develop digital competences. Thus, the main goal of this work is to present the methodology used to build the informal Guide, as well as depict some of the most relevant characteristics of the selected participants.